Montmorillonite (MMT) effect on the structure of poly(oxyethylene) (PEO)-MMT nanocomposites and silica-PEO-MMT hybrid materials - Hikosaka, M. Y.; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Dahmouche, K.; Craievich, A. F. (Elsevier B.V., 2006)
In this work we report the effects of incorporation of variable amounts (0.5-25%w/w) of montmorillonite in poly(oxyethylene) based materials in order to decrease the polymer crystallinity. Two different classes of materials were studied: silica-poly(oxyethylene)-montmorillonite hybrids prepared by the sol-gel route and poly(oxyethylene)-montmorillonite nanocomposites prepared by mixing the dry clay or the clay aqueous suspension into the melt poly(oxyethylene). The effects of monternorillonite loading on the poly(oxyethylene) crystallization control and on the nanostructural features were investigated by X-ray powder diffraction, small-angle X-ray scattering and differential scanning calorimetry. Experimental results show that free montmorillonite layers coexist with open aggregates and tactoids in the poly(oxyethylene)-montmorillonite nanocomposites, with different features depending on the filler proportion and preparation route. The intercalation of polymer chains in montmorillonite galleries markedly hinders the crystallization of the poly(oxyethylene) matrix. For hybrids materials the silica phase favors the exfoliation of montmorillonite tactoids, so that samples are predominantly constituted by dispersed platelets. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: crystallization; nanoparticles; nanocomposites; sol-gel; aerogel and solution chemistry; organic-inorganic hybrids